Comparison of Closure Measurements with Finite Element Model Results in an Underground Coal Mine in Central Utah - William G. Pariseau; Michael K. McCarter; Jessica M. Wempen (International Conference on Ground Control in Mining, 2018)
"Quantitative analysis of mine-wide subsidence at the kilometer scale and details of stress distribution about an advancing longwall face are estimated using an adaptation of the finite element method. The method is well suited to the tasks at hand. For greater realism, variability of strata properties is taken into account as are the effects of joints and cleats on elastic moduli and strengths. Evolution of pillar stress and entry closure remote from the face is readily quantified in a series of analyses that simulate face advance. Computed results compare favorably with the evolution of closure measurements about an instrumented pillar in a two-entry headgate. The appropriateness of the finite element method is confirmed. This method is based on first principles that avoid empirical schemes of uncertain applicability and numerical models “calibrated” by fitting computer output to mine measurements.INTRODUCTIONMine-induced seismicity is intimately related to strata mechanics associated with longwall coal mining and room and pillar mining, as well. Strata deformed beyond an elastic limit often tend to fail rapidly by brittle fracture and, thus, to emit acoustic signals in the form of elastic waves. Understanding the induced seismicity in coal mining offers the potential for early warning of hazardous conditions. Many years of experience with seismic phenomena associated with hardrock mining suggest considerable complexity should be expected. However, recent coal mine studies (Pariseau, 2014; Pariseau, 2015; Pariseau and McCarter, 2015; Pariseau and McCarter, 2016) have shown high correlations of seismicity with element failures in finite element simulations. The main lesson learned from these studies is one elaborated by Iannacchione et al (2005); deviation from normal activity is an early warning of ground control difficulty. For example, an abrupt increase in seismic event rate, or equivalently, an increase in element failure in finite element simulation of panel advance, is a cautionary indication for ground control. Present and past study results demonstrate the effectiveness of finite element simulations for mine design and early detection of potential ground control issues."